Buying right : getting started in real estate investment - Wayner, Stephen A. (New York : F. Watts, 1987)
The goal of the book is to give you everything you'll need to achieve the financial freedom you dreamed of
Includes index.
osc 12/11/2019
Loans
Keywords: Real estate investment